Psané podoby přejatých slov - Svobodová, Diana (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2013)
The article focuses on the problem of graphic adaptation of new foreign loan- words (namely anglicisms) and their varied forms used in the contemporary Czech language. The author concentrates on several selected types of lexemes with the help of their evaluation by the youth aged 12 to 18 years, and comments on the linguistic character of their forms (standard or substandard, semantically modified, stylistically symptomatic etc.).
Keywords: Czech language; stilistic; borrowings; graphic adaptation